THE RELATIONSHIP BETWEEN SALIVARY FLOW RATE AND CALCIUM ION SECRETION IN SALIVA. - Indriana, Tecky (Fakultas Kedokteran Gigi Universitas Jember, 2010)
The aim of this research is to describe the relationship between salivary flow rate and number of calcium ion secretions in saliva. This study involved 10 young-adult dental school students of Jember University. Using the spitting method, the amount of saliva secreted was measured. Calcium ion secreted within the saliva fluid was measured using Flame Fotometer. The research results showed that there is relation between salivary flow rate andthe number of calcium ion secretion in saliva